2023
DOI: 10.3390/su151310559
|View full text |Cite
|
Sign up to set email alerts
|

Using Industrial Waste Heat in District Heating: Insights on Effective Project Initiation and Business Models

Abstract: The recovery of industrial waste heat and its reuse in district heating networks can be economical for both the industry and the district heating operator. While the potential for external use of industrial waste heat remains significant, there are already many implemented practical examples. This paper describes an Austria-wide survey of industrial companies that supply waste heat to district heating networks in order to assess the (i) initiation and implementation, (ii) business model design, and (iii) risks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 19 publications
(44 reference statements)
0
3
0
Order By: Relevance
“…It also should be noted that mutual trust between waste heat suppliers and consumers is a prerequisite for any successful waste heat cooperation initiative. A survey conducted among industrial waste heat suppliers and district heating operators in Austria revealed that trust, transparency, and clarity play a central role in the success of waste heat utilization projects [10]. The study also concluded that good understanding, regular exchange, and a certain level of trust will promote such relationships.…”
Section: Practical Implications Of Our Methodology and Resultsmentioning
confidence: 99%
“…It also should be noted that mutual trust between waste heat suppliers and consumers is a prerequisite for any successful waste heat cooperation initiative. A survey conducted among industrial waste heat suppliers and district heating operators in Austria revealed that trust, transparency, and clarity play a central role in the success of waste heat utilization projects [10]. The study also concluded that good understanding, regular exchange, and a certain level of trust will promote such relationships.…”
Section: Practical Implications Of Our Methodology and Resultsmentioning
confidence: 99%
“…This is significant because, whereas previous attempts to use gold nanomaterials to enhance electrocatalysis has also decreased stability (due to the increased reactivity of the nanostructured gold), this study demonstrates how appropriately electrostatically charged SAMs can lower the apparent electron transfer resistance and simultaneously improve long-term stability. This is critical when considering most industrial waste heat applications have commercial payback periods of 3 to 15 years, 44 demonstrating the time frames thermocell devices should continuously operate for (and ideally exceed).…”
Section: Resultsmentioning
confidence: 99%
“…Many studies have examined the industrial waste heat potential from the perspectives of energy efficiency and policy [10,11]. Some have concentrated on national-or regionallevel heat emissions [12,13] via inventory-based methods, energy balance residuals, the construction of energy models [14], multi-methods [15], and statistical regression methods [13,16,17].…”
Section: Introductionmentioning
confidence: 99%